RETRACTED: To increase the effectiveness of the mechanism for the implementation of the bank’s financial product - Grober Tatiana; Grober Oleg; Tsybenko Olga; Klimova Elena (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001